Maxillo-orbital gunshot trauma in a pediatric patient - Maram Adil Mansour; Elnagar E. Elgasim; Esameldin Adam Nagi; Ibtisam Hussein; Malaz Mansour (Advances in Oral and Maxillofacial Surgery)
Gunshot injuries to the maxillofacial region vary in severity from minor harm to critical situations necessitating urgent medical intervention. Effective handling of facial gunshot wounds mandates a multidisciplinary approach to deliver thorough care to the individual.We present a pediatric patient presenting to the Emergency Department following an accidental machine gun injury.